L’anatomie d’un crime au féminin - Martha Vassiliadi (Cahiers Balkaniques)
It is well known that in the collective imagination murder by poisoning is almost exclusively practiced by women. In the Greek popular tradition, the women’s crime –crime mainly motivated by passion– joins the view of an archaic violence that reverses the image of the nursing mother by projecting demonic figures against nature. Motivated by revenge or moreover jealousy, murderesses take revenge by killing and cooking often in order to express a deep discomfort in the patriarchal society.However, in our era of food fetish, this relationship between eating and killing is defined as a voluptuous and funeral process that links eroticism and gastronomy. Focused on a comparative approach, this paper proposes to think how fiction, obsessed with the luxury of eating crystallizes the hybrid culinary myth of women’s crime in order to analyze the perspective of a narrative.